Effects of External Oiling and Rehabilitation on Hematological, Biochemical, and Blood Gas Analytes in Ring-Billed Gulls (Larus delawarensis) - Dannemiller, Nicholas G.; Horak, Katherine E.; Ellis, Jeremy W.; Barrett, Nicole L.; Wolfe, Lisa L.; Shriner, Susan A. (Frontiers in Veterinary Science, 2019)
Avian species experience extensive morbidity and mortality following large-scale oil spills, often resulting in oiled birds being rescued and admitted to rehabilitation. Our objective was to experimentally establish time-specific, descriptive blood analyte data following sublethal oil exposure and subsequent rehabilitation. Thirty wild Ring-billed Gulls (Larus delawarensis) were randomly allocated to three treatment groups of 10 birds each. One treatment group served as controls and two treatment groups were externally oiled daily for three days with weathered MC252 oil collected from the Deepwater Horizon oil spill, mimicking the upper threshold of the US Fish and Wildlife Service’s moderate oiling classification. Following external oiling, one oiled treatment group was cleaned via standard rehabilitation practices. Serial venous blood samples were collected for a month to measure packed cell volume, total solids, blood gas and select plasma biochemistry analytes, total white blood cell estimates and differentials, and reticulocyte estimates. We found that both sublethal oil exposure and aspects of captivity were associated with a mild non-regenerative anemia. No other differences in venous blood gas and biochemical analytes as well as white blood cell concentrations were observed among the three groups. These findings suggest that the mild anemia seen in oiled birds undergoing rehabilitation is possibly multifactorial and that moderately oiled gulls have subtle, but potentially not insignificant clinicopathological abnormalities following sublethal oil exposure. Oiled gulls did not develop any clinicopathological derangements post-rehabilitation, suggesting current standard practices for rehabilitation cause minimal morbidity in clinically stable, moderately oiled gulls.